Lifestyle of Employees working in Hamadan Departments: An Application of the Trans-Theoretical Model - Jalal Abdi; Hassan Eftekhar; Mahmood Mahmoodi; Davood Shojayzadeh; Roya Sadeghi (Journal of Education and Community Health)
Introduction: Healthy lifestyle is a valuable source to reduce the prevalence of health problems and promoting health. Given the key role of employees as valuable human resources, the aim of this study was to evaluate lifestyle obesity and position of governmental employees in changing process based on the Trans-Theoretical Model (TTM) in Hamadan. Materials & Methods: This descriptive-analytical study was performed on 1200 government employees selected using suitable stratified sampling. Data collection was performed using a three-section questionnaire containing demographic characteristics, FANTASTIC lifestyle questionnaire and Marcus et al.’s five-part questionnaire. Data was analyzed by correlation tests, Chi-square, T-test and ANOVA using SPSS-20. Results: Lifestyle status of most employees (61.7 percent) was satisfying. About a half of the employees were in the preparatory stage of TTM. Considering the physical activity and healthy eating habits, most employees had a poor condition. Women had higher scores than men in most items. The associations between lifestyle and age, gender, work experience, income satisfaction and marital status were significant. Moreover, the associations between obesity and work experience, marital status, number of children and gender were significant (p<0.05). Conclusion: Planning health education interventions for employees through effective approaches seems to be necessary.